2012
DOI: 10.1038/jcbfm.2012.195
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Analysis of the Metabotropic Glutamate Subtype 5 Tracer [18F]FPEB in Bolus and Bolus-Plus-Constant-Infusion Studies in Humans

Abstract: [ 18 F]FPEB is a positron emission tomography tracer which, in preclinical studies, has shown high specificity and selectivity toward the metabotropic glutamate receptor 5 (mGluR5). It possesses the potential to be used in human studies to evaluate mGluR5 function in a range of neuropsychiatric disorders, such as anxiety and Fragile X syndrome. To define optimal scan methodology, healthy human subjects were scanned for 6 hours following either a bolus injection (n ¼ 5) or bolus-plus-constant-infusion (n ¼ 5) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
67
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 36 publications
6
67
1
Order By: Relevance
“…[ 18 F]FPEB was administered i.v. as bolus plus infusion for 120 min, with a K bol of 190 min (19,76). Based on previous studies showing that equilibrium was reached at 60 min, emission data were acquired 90-120 min after the start of injection on the high-resolution research tomograph (Siemens/CTI), which has intrinsic spatial resolution of ∼2.5 mm FWHM.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 18 F]FPEB was administered i.v. as bolus plus infusion for 120 min, with a K bol of 190 min (19,76). Based on previous studies showing that equilibrium was reached at 60 min, emission data were acquired 90-120 min after the start of injection on the high-resolution research tomograph (Siemens/CTI), which has intrinsic spatial resolution of ∼2.5 mm FWHM.…”
Section: Methodsmentioning
confidence: 99%
“…Given the lack of a reference region for mGluR5 targets (78), V T (ratio of radioligand concentration in ROI to the concentration in plasma at equilibrium) was used as the outcome measure. V T was estimated by the equilibrium analysis method described previously (76) and a venous plasma input function (19).…”
Section: Methodsmentioning
confidence: 99%
“…To minimize the radiation dose received by human subjects, it is recommended that bladder voiding be done at 1 or 1.5 h after bolus administration of 18 F-FPEB, which significantly lowers both the urinary bladder wall and the effective doses. Previous studies indicate that 1.5 h of imaging after bolus injection of 18 F-FPEB should allow quantitation of mGluR5 levels in all brain regions; for such studies, urinary voiding at the end of the imaging study is recommended (14,15).…”
Section: Discussionmentioning
confidence: 99%
“…It has a high affinity (0.11-0.15 nM) for the mGluR5 and nearly optimal lipophilicity for imaging, with a logP of 2.8 (13). Initial human imaging studies have shown high contrast between regions rich in mGluR5 levels, such as the anterior cingulated, and regions with low levels, such as the cerebellum and pons, as well as the ability to estimate regional receptor levels using both bolus administration with 2-tissue-compartment modeling and bolus-infusion administration (14,15). Given the importance of the mGluR5 in several disease states and its promise as a PET radioligand for studies of mGluR5, we undertook studies of human radiation dosimetry of 18 F-FPEB.…”
mentioning
confidence: 99%
“…The radioactivity concentration in each brain region was normalized to the injected dose and body weight and expressed as standardized uptake value. Receptor occupancy was calculated with the Michaelis-Menten equation (12), using the free fraction of 18 F-FPEB determined in humans (13).…”
Section: Small-animal Pet Analysismentioning
confidence: 99%